2019
DOI: 10.1186/s12903-018-0681-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene, prevalence of gingivitis, and associated risk factors among pregnant women in Sarlahi District, Nepal

Abstract: BackgroundThe oral health status of pregnant women in low-resource communities such as Nepal has not been well characterized. This sub-population is also of specific interest given associations between poor oral health and adverse pregnancy outcomes previously documented in other settings. We explored relationships between gingivitis and risk factors among pregnant women in rural Nepal.MethodsThe design was a community-based, cross-sectional study in a sub-area of Sarlahi District, Nepal. Pregnant women < 26 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 29 publications
4
57
3
2
Order By: Relevance
“…29 This may be due to the fact that the sample in the study consisted mostly of young women. However, this result is in contrast to other studies 22,37 in which the authors have suggested that aging is a natural process which results in changes in host immunity which may cause the loss of periodontal support tissue. 29…”
Section: Agecontrasting
confidence: 99%
See 3 more Smart Citations
“…29 This may be due to the fact that the sample in the study consisted mostly of young women. However, this result is in contrast to other studies 22,37 in which the authors have suggested that aging is a natural process which results in changes in host immunity which may cause the loss of periodontal support tissue. 29…”
Section: Agecontrasting
confidence: 99%
“…The severity of gingivitis showed an association with the gravida of the female patient. The ndings in our study impersonates with another study done in Nepal 22 . Only a minority of pregnant women seek care for bleeding gums in the absence of pain.…”
Section: Graviditysupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, the immune-inflammatory response toward periodontitis may initiate or exacerbate many systemic diseases including diabetes mellitus [15], osteoporosis, cancer [25], rheumatoid arthritis, and systemic lupus erythematosus [26]. In addition, pregnancy, which is the most delicate and important stage in a person's life, will be highly affected by any systemic disturbances or inflammation represented in the pregnant [27].…”
Section: A Lot Of Research Took Place In Order To Answer This Questionmentioning
confidence: 99%